Hepatoprotective effects of loach (Misgurnus anguillicaudatus) lyophilized powder on dimethylnitrosamine-induced liver fibrosis in rats - Zhang, Qian; Shang, Meng-Meng; Ling, Qu-Fei; Wu, Xiao-Ping; Liu, Chun-Yu (Archives of pharmacal research, 2021)
This study investigates the hepatoprotective effects and the potential therapeutic mechanisms of loach ( Misgurnus anguillicaudatus ) lyophilized powder (MLP) on dimethylnitrosamine (DMN) induced liver fibrosis in rats. After treatment with MLP (50, 100, 200 mg/kg), alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin (Alb), total protein (TP) and hydroxyproline (Hyp) levels were detected, to assess the destruction of hepatocytes and the extent of liver fibrosis. Matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9), hyaluronic acid (HA), Laminin (LN), procollagen type-III (PC-III), collagen type-IV (C-IV), and transforming growth factor-β 1 (TGF-β 1 ) contents in serum were all tested using ELISA kits. Alpha-smooth muscle actin (α-SMA) and the tissue inhibitor of metalloproteinase-1 (TIMP-1) protein contents and distribution were evaluated using western blot and immunohistochemical analysis. MLP significantly decreased the serum concentrations of ALT, AST, Hyp, HA, LN, PC-III, C-IV, MMP-2, TIMP-1, α-SMA and TGF-β 1 , while increasing the contents of Alb and MMP-9. No significant changes on TP serum concentrations were observed. These results suggest that MLP has anti-hepatic fibrosis effects and its mechanism may be associated with the attenuation of extracellular matrix (ECM) synthesis, the acceleration of ECM degradation, inhibition of hepatic stellate cells (HSCs) activation and TGF-β 1 expression. Graphical Abstract